Business rights and ethnic exclusion in sub-Saharan Africa: Addressing group-based inequality through business rights reform - Scott D. Taylor (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
The business rights pillar of the Legal Empowerment of the Poor agenda is not preoccupied with equality of outcome; it concentrates instead on equality of opportunity. This paper addresses the lacuna in the business rights literature by 'bringing outcomes back in'. Certainly, equal outcomes are difficult to achieve and require understanding of a host of group as well as individual characteristics, and the complex obstacles to distributing benefits more broadly and beneficially, especially to members of groups that have faced historical discrimination in business. In order to understand some of the ways in which the interests of the poor can be advanced in business, and how mere business rights might be complemented, this research extends the analysis to include what I call active business rights reforms.
Keywords: 330; Africa; legal empowerment; business rights; entrepreneurship; empowerment; affirmative action